Penghapusan Hukuman Mati Pada Sistem Peradilan Pidana Di Indonesia Atas Lahirnya UU No 1 Tahun 2023 Tentang KUHP - Rasina Padeni Nasution; Rizki Akbar Muluk Siregar; Ratu Frisya Ritonga; Amany Zuhaira Ritonga; Reza Ananda Siregar (Pusat Riset dan Inovasi Nasional, 2024)
Indonesia is a country that acknowledges the existence of Human Rights, but this does not lead to the abolishment of the death penalty in its positive law. Both the old and new Criminal Codes (KUHP) still regulate the death penalty, albeit in different concepts. This research aims to identify the differences between the death penalty in the old and new Criminal Codes and to understand and analyze the death penalty in the new Criminal Code from a human rights perspective. The research employs a normative juridical method. The findings indicate that the death penalty in the new Criminal Code is no longer the primary punishment as in old Criminal Codes and has been replaced with an alternative penalty. Under the new Criminal Code, those sentenced to death will undergo a probationary period of 10 (ten) years, and if they demonstrate good behavior during this period, the death penalty will be commuted to life imprisonment or imprisonment for 20 (twenty) years. This change is motivated by the perception that the death penalty constitutes a violation of human rights.